Entrepreneurial Skills Acquisition and Utilization Among Home Economics Education Graduates of Ahmadu Bello University Zaria, Nigeria - Rakia, Ahmed; Gaite, Sofia Sal; Salami, Samuel (NIU Journal of Social Sciences; Vol 3 No 1 (2017): KIU Journal of Social Sciences, Vol. 3 No. 1, March 2017, 2017)
The paper looked at the entrepreneurial skills acquisition and utilisation of skills among the home economic graduates of Ahmadu Bello University Zaria, Kaduna State Nigeria. It critically examines the concepts of the key terms, Entrepreneurship skills acquisition and home economics education. The paper has also tried to look at the unemployment rate in Nigeria. The concept of entrepreneurial skills acquisition is seen as the training that provides experience and skills that are suitable for self-employment of graduates, with the help of creativity, innovation and foresight. While home economics is the field of study that is concerned with strengthening individual and family life that provide functional knowledge for self-reliance. The paper went further to look into utilisation of skills in home economic which involves food and nutrition skills, clothing and textiles skills, home management skills, child development skills and housing and design skills. Utilisation of the above mention skills will equip, inculcate the sense of self-reliance and promotes healthy interpersonal relationship. At the end the paper gives some recommendations on how to improve the quality of both entrepreneurial skills acquisitions and utilisation of skills of graduates.